A General Non‐Radioactive ATPase Assay for Chromatin Remodeling Complexes. Issue 1 (2nd March 2017) - Stanton, Benjamin Z.; Hodges, Courtney; Crabtree, Gerald R.; Zhao, Keji
Abstract : Chromatin remodeling complexes couple the energy released from ATP hydrolysis to facilitate transcription, recombination, and repair mechanisms essential for a wide variety of biologic responses. While recombinant expression of the regulatory subunits of these enzymes is possible, measuring catalytic (ATPase) activity of the intact complexes recovered from normal or mutant cells is critical for understanding their mechanisms. SWI/SNF‐like remodeling complexes can be megadaltons in size and include many regulatory subunits, making reconstitution of purified subunits challenging for recapitulating in vivo function. The protocol in this article defines the first highly quantitative ATPase assay for intact remodeling complexes that does not require radiation or reconstitution of recombinantly expressed subunits. This protocol is specifically useful for defining the catalytic role of active‐site mutations in the context of other regulatory subunits and quantitatively rank‐ordering inactivating catalytic‐site mutations. © 2017 by John Wiley & Sons, Inc.